Yield and nutritional value of hybrid Urochloa grasses in the dry tropics of Mexico - Maldonado-Peralta , María de los Ángeles; Aguirre, Herminio Aniano; Rojas García, Adelaido Rafael; García-Montalvo, Iván Antonio; Ortega-Acosta , Santo Ángel; Martínez-Vázquez , Jaime (Ecosistemas y Recursos Agropecuarios, 2025)
The objective of this study was to evaluate the yield and protein of Mulato II, Convert 330 and Convert 431 grasses (Urochloa hybrids) at cutting frequencies in the dry tropics. The variables evaluated were: total forage yield and by components, intercepted radiation, plant height, leaf:stem ratio, growth rate, morphological composition and crude protein (CP) by component. The data were analyzed using a completely randomized block design with a split plot arrangement and four repetitions; the procedure used was PROC GLM from SAS. The highest yield of total dry matter was obtained 49 days after cutting in the Mulato II and Convert 330 pastures with 5 450 and 3 900 kg ha-1, respectively, and in the Convert 431 pasture it was on day 56 with 3 000 kg ha-1 (p < 0.05). The leaf component was the one with the highest CP content in the three grasses and after 14 days the highest value was presented (24%, on average; p < 0.05); while at 56 days the lowest PC content was obtained in the leaf (13%. p < 0.05). In conclusion, the yield of total matter, intercepted radiation, growth rate increased with the cutting frequency up to a maximum point and subsequently declined, while the CP content in leaf and stem decreased as the evaluation time passed, therefore, it is recommended to sow Mulato II grass in the region.